(untitled) (Jurnal Sustainable, 2024)
This study aims to evaluate the effectiveness and challenges of curriculum implementation in Madrasah Ibtidaiyah (MI) in Indonesia, as well as provide strategic recommendations for improvement. A qualitative approach with a descriptive-analytical design is used to identify factors that affect the success of curriculum implementation. Data was collected through in-depth interviews with madrasah heads and teachers, participatory observations, and analysis of related documents such as syllabi and evaluation reports. The findings show that limited teacher training, lack of learning facilities, and dominance of traditional approaches are the main obstacles to achieving curriculum goals. The results of the analysis highlight the importance of applying project-based learning methods (PBL) and character education to improve 21st-century skills, such as critical thinking, communication, and collaboration. However, the implementation of this method still faces technical and pedagogical obstacles. This research also found the need to strengthen teacher competence through continuous training and the provision of relevant educational resources. In conclusion, the implementation of the curriculum in MI requires synergy between education policies, teacher training, and infrastructure support. The recommendations of this research include improving training programs, procuring technology-based facilities, and collaborating with the government, madrasas, and the community. This research contributes to supporting the development of Islamic education that is more adaptive to the challenges of the globalization era.